S-palmitoylation Is Required for the Control of Growth Cone Morphology of DRG Neurons by CNP-Induced cGMP Signaling - Dumoulin, Alexandre; Dagane, Alina; Dittmar, Gunnar; Rathjen, Fritz G. (Frontiers in Molecular Neuroscience, 2018)
Genetic investigations have demonstrated that a specific form of axonal branching - the bifurcation of afferents from dorsal root ganglia (DRG), cranial sensory ganglia (CSG) and mesencephalic trigeminal neurons (MTN) - is regulated by a cGMP-dependent signaling pathway. This cascade is composed of the ligand C-type natriuretic peptide (CNP), the receptor guanylyl cyclase Npr2, and cGMP-dependent protein kinase Iα (cGKIα). In the absence of any one of these components, axons no longer bifurcate, instead they turn in either an ascending or a descending direction. To gain further mechanistic insights into the process of axon bifurcation we applied different cell culture approaches to decipher downstream activities of cGKI in somatosensory growth cones. We demonstrate that CNP induces an enlargement of DRG growth cones via cGKI which is considered as the priming step of axon bifurcation. This growth cone remodelling was both blocked and stimulated by pharmacological reagents that interfere with S-palmitoylation. cGKI colocalizes with the palmitoylome and vesicular structures including the endoplasmic reticulum, early endosomes, lysosomes primarily in the central domain of the growth cone as well as with the Golgi apparatus at the level of the soma. Consistently, an acyl-biotin-exchange chemistry-based screen indicated that cGMP signalling induces S-palmitoylation of a restricted pool of proteins in the DRG-derived cell line F11. Overall, our data indicate that CNP-induced cGMP signalling via cGKI affects growth cone morphology of somatosensory afferents via S-palmitoylation which might be a priming step for axon bifurcation in the spinal cord.